Exploring the association between height, height dissatisfaction, and grandiose and vulnerable narcissistic traits - Daniel Talbot; Ardavan Khamisi (Discover Psychology)
Abstract Our study explored the relationship between grandiose and vulnerable narcissistic traits, and height and height dissatisfaction, focusing on differences in how these traits manifest in relation to body image. Drawing on data from 432 participants, shorter stature and wanting to be taller were associated with both grandiose and vulnerable narcissistic traits. Additionally, these associations were stronger among men, particularly for entitlement/exploitativeness (a sub-factor of grandiose narcissism). Further, a post-hoc regression demonstrated that height and vulnerable narcissistic traits uniquely predicted the desire to be taller. These findings highlight the nuanced role of height dissatisfaction in the expression of narcissistic traits, particularly vulnerable narcissism, and underscore the importance of considering physical self-perception in understanding narcissistic behaviors and self-image.